TINJAUAN TEOLOGIS TENTANG GAYA HIDUP ORANG KRISTEN YANG TELAH LAHIR BARU BERDASARKAN SURAT KOLOSE 3:1-17 DAN IMPLIKASINYA PADA JEMAAT GPIA KASIH SURGAWI JEMBER - Gratisman Laoli; Rabiel Sobon (Sekolah Tinggi Teologi Duta Panisal, 2022)
Currently the Christian lifestyle is getting worse. The Christian lifestyle is getting more and more depressed by following the worldly lifestyle. The behavior of the Christian life has also fallen into the worldly behavior. So that Christians are not able to influence the worldly people. Or not being an example for worldly people. The title of this research is “The Theological Review of Born-Again Christian Lifestyles Based on Colossians 3:1-17 and Its Implications for the GPIA Kasih Heavenly Jember Congregation.” This study uses a qualitative research method using a case study approach. The data will be analyzed by descriptive method using the theory of Miles and Huberman. Based on the data analysis carried out, it is concluded that what is meant by new birth is a work of the Holy Spirit for someone who has given his life to God, and has left his old actions that are not in accordance with God's will. His lifestyle does not follow worldly actions such as: fornication, uncleanness, lust, evil lust, and also greed which is the same as idolatry. People who have been born again are God's chosen people. His lifestyle is full of compassion, generosity, humility, gentleness and patience. Based on the research conducted, it is evident that as a Christian must experience a new birth and his life has undergone a change by not following worldly desires anymore.